Glutamine: An Obligatory Parenteral Nutrition Substrate in Critical Care Therapy. (1st October 2015) - Stehle, Peter; Kuhn, Katharina S.
Abstract : Critical illness is characterized by glutamine depletion owing to increased metabolic demand. Glutamine is essential to maintain intestinal integrity and function, sustain immunologic response, and maintain antioxidative balance. Insufficient endogenous availability of glutamine may impair outcome in critically ill patients. Consequently, glutamine has been considered to be a conditionally essential amino acid and a necessary component to complete any parenteral nutrition regimen. Recently, this scientifically sound recommendation has been questioned, primarily based on controversial findings from a large multicentre study published in 2013 that evoked considerable uncertainty among clinicians. The present review was conceived to clarify the most important questions surrounding glutamine supplementation in critical care. This was achieved by addressing the role of glutamine in the pathophysiology of critical illness, summarizing recent clinical studies in patients receiving parenteral nutrition with intravenous glutamine, and describing practical concepts for providing parenteral glutamine in critical care.